К методике использования почвенных ловушек в экологических исследованиях - Руденская, Л.В. (Вестник зоологии, 1981)
Methods are considered forusing ground traps in ecological studiesof terrestrial invertebrates including a study of a specific complex of terrestrial springtails which are not completely taken into account by the elector technique.